Empowering Quality of Web-based Nutrition and Health Education Through Knowledge Upgrading for “Gizigo” in Yogyakarta - Ira Dwijayanti; Regina Nur Lailatul Mufidah; Khofifah Nurwahidin; Mufid Salim; Fasty Arum Utami (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
Gizigo actively provides nutrition education on various scientific articles, webinars and posters through social media such as Instagram. Website-based education has been widely applied in Indonesia to spread nutrition information. The purpose of this community service program is to provide training and assistance for Gizigo in order to improve the quality of education so that they can develop more productive, innovative and adaptive education methods. The core activity is to increase the knowledge and skills to support improving the quality and productivity of partners by giving the training about Nutritional Education Content and Financial And Tax Management for Startup. The topic and case study provided were quite interesting and applicable in the education field. The result of of the activity are health education content material and pre-post test score. It is important to begin to capture and report on the cost and cost effectiveness on internet based health education